A randomized crossover study of functional electrical stimulation during walking in spastic cerebral palsy: the FES on participation (FESPa) trial - Irene Moll; Rik G. J. Marcellis; Marcel L. P. Coenen; Sabine M. Fleuren; Paul J. B. Willems; Lucianne A. W. M. Speth; M. Adhiambo Witlox; Kenneth Meijer; R. Jeroen Vermeulen (BMC, 2022)
Abstract Background Spastic cerebral palsy is the most common cause of motor disability in children. It often leads to foot drop or equinus, interfering with walking. Ankle-foot orthoses (AFOs) are commonly used in these cases. However, AFOs can be too restrictive for mildly impaired patients. Functional electrical stimulation (FES) of the ankle-dorsiflexors is an alternative treatment as it could function as a dynamic functional orthosis. Despite previous research, high level evidence on the effects of FES on activities and participation in daily life is missing. The primary aim of this study is to evaluate whether FES improves the activity and participation level in daily life according to patients, and the secondary aim is to provide evidence of the effect of FES at the level of body functions and activities. Furthermore, we aim to collect relevant information for decisions on its clinical implementation. Methods A randomized crossover trial will be performed on 25 children with unilateral spastic cerebral palsy. Patients aged between 4 and 18 years, with Gross Motor Functioning Classification System level I or II and unilateral foot drop of central origin, currently treated with AFO or adapted shoes, will be included. All participants will undergo twelve weeks of conventional treatment (AFO/adapted shoes) and 12 weeks of FES treatment, separated by a six-week washout-phase. FES treatment consists of wearing the WalkAide® device, with surface electrodes stimulating the peroneal nerve during swing phase of gait. For the primary objective, the Goal Attainment Scale is used to test whether FES improves activities and participation in daily life. The secondary objective is to prove whether FES is effective at the level of body functions and structures, and activities, including ankle kinematics and kinetics measured during 3D-gait analysis and questionnaire-based frequency of falling. The tertiary objective is to collect relevant information for clinical implementation, including acceptability using the device log file and side effect registration, cost-effectiveness based on quality adjusted life years (QALYs) and clinical characteristics for patient selection. Discussion We anticipate that the results of this study will allow evidence-based use of FES during walking in children with unilateral spastic cerebral palsy. Trial registration ClinicalTrials.gov : NCT03440632 .